Bacterial biomass and activity in the deep waters of the eastern Atlantic—evidence of a barophilic community - Patching, J.W.; Eardly, D. (Deep-sea research. Part I, Oceanographic research papers, 1997)
Bacterial biomass and activity were investigated in deep waters at two sites in the eastern Atlantic, of similar depth (4560–4800 m), but varying in their nutritional status. The Northern (N) site was eutrophic and subject to a strong seasonal input of surface derived organic matter (phytodetritus) to the sediment. The Southern (S) site was oligotrophic. Deep water at this site does not appear to receive any strong seasonal input. Bacterial numbers in the deep water column at the N site showed no significant seasonal variation but were greater than those at the S site. Deep water bacteria were typically small and free-living. From biovolume determinations, it was estimated that mean concentrations of bacterial organic carbon at depths greater than 500 m were 0.12 (0.03–0.29) μg C 1 −1 and 0.02 (0.01–0.04) μg C 1 −1 at the N and S sites, respectively. Rates of thymidine and leucine incorporation were used as indicators of bacterial activity. Bacterial communities in water in contact with the sediment (SCW; sediment contact water) at both sites (but especially at the S site) were strongly barophilic at in situ temperatures (2.5–4.1°C). The barophilic response of thymidine incorporation was enhanced when SCW samples from the N site were incubated at 11.5°C. It is proposed that this result indicated an elevating effect of pressure on cardinal temperatures and that the SCW community was obligately psychrophilic when unpressurised. Comparison of cell-specific incorporation rates determined under in situ conditions showed bacteria in the SCW to have levels of activity comparable with bacteria from a depth of 150 m. Thymidine incorporation rates were highest in SCW samples taken at the N site in May 1988 and September 1989. Thymidine incorporation by SCW samples taken immediately before (10 April 1994) the main spring-bloom-associated deposition of phytodetritus was significantly lower and comparable with that determined for the oligotrophic S site. The attributes exhibited by the SCW community appeared to be highly localised. We conclude that the bacterial communities of the SCW are active and adapted to their environment. Activity is influenced by the trophic nature of the site and may show temporal changes linked with episodic food supply. We postulate that the existence of such communities is linked to the role of the sediment-water interface as the initial site of deposition of sea-surface derived labile organic material.